A Study of Feminine Accounting in Household Financial Management Practices: A Case Study of Housewives in RT 005 RW 006, Kelurahan Gumuruh - Siti Kodariah; Ricky Riansyah Putra; H. Qur'ani Noor; Sina Delphia Sukmana (Greenation International Journal of Economics and Accounting, 2024)
This research aims to explore the adaptation of feminine accounting in household financial management practices among housewives in RT 005 RW 006 Kelurahan Gumuruh. A qualitative approach using case study methods was employed to understand how feminine accounting can create a more inclusive and gender-responsive financial management system. Data were collected through interviews, observations, and document analysis. The results show that feminine accounting enables more equitable and gender-sensitive household financial management. Additionally, the adaptation of feminine accounting supports family welfare by enhancing women's participation in financial decision-making. This study recommends training and education on feminine accounting to strengthen housewives' roles in effectively managing family finances.